If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4(c + -5) = 5x + 1 Reorder the terms: 4(-5 + c) = 5x + 1 (-5 * 4 + c * 4) = 5x + 1 (-20 + 4c) = 5x + 1 Reorder the terms: -20 + 4c = 1 + 5x Solving -20 + 4c = 1 + 5x Solving for variable 'c'. Move all terms containing c to the left, all other terms to the right. Add '20' to each side of the equation. -20 + 20 + 4c = 1 + 20 + 5x Combine like terms: -20 + 20 = 0 0 + 4c = 1 + 20 + 5x 4c = 1 + 20 + 5x Combine like terms: 1 + 20 = 21 4c = 21 + 5x Divide each side by '4'. c = 5.25 + 1.25x Simplifying c = 5.25 + 1.25x
| -5-45/3 | | 11n-11=11+12(n+3) | | 3=5x+4x+3 | | 7z^2-12z+20= | | -3(5w+v)-2(-3v+3w)= | | -5.6*-14.3= | | 342=23*b | | xy-xz=b-c | | -5.6x-14.3= | | -9x+13=-27 | | x-8=4-2(3x+5) | | 3d+8=6d-2 | | n+1=-17-10n-2+9n | | xy-zy=b-c | | -n-24=5-q | | 8x+38=3(x+1) | | xy-zy=b | | 2t^3-10t=t^2 | | 15-3x=15-3x | | 7x-6-4x=2x+6 | | 10-15x=35 | | 46-7x=12+10x | | 0.3333333333333333= | | 3xy+yx= | | 3x-4=6x-1 | | ax+bc+3=-6 | | -129=6(1-4n)-3n | | -(5w+u)+3(3u+5w)= | | 4z-5=19 | | 4x=4x+7 | | -4+5k=11 | | 3x^3+5x-8=0 |